2016
DOI: 10.1177/2158244016638390
|View full text |Cite
|
Sign up to set email alerts
|

Privately Provided Accommodation Service Quality and Customer Satisfaction

Abstract: Privately provided accommodation is a growing service in Uganda's higher education sector due to education liberalization and demand for education. This research took a case study of Nsamizi Training Institute of Social Development (NTISD) to determine the relationship between privately provided accommodation service quality and customer satisfaction. Specifically, the objectives of the study were (a) to find out the relationship between security and NTISD students' satisfaction with privately provided accommo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In addition, CCBs will be enhanced when there is a match between customer identity and organizational identity, or when the interdependent relationships exist between service organization and customers (Ahearne et al, 2005). If the customers receive more attention and responses from service firms, such as responding to customers' kind advice with timely measures, customers will be more active in services and voluntarily provide the enterprise with rationalization proposal (Mugambwa et al, 2016). In this way, the customer-enterprise relationship turns into a virtuous circle and service firms will finally benefit from their effort in service climate (Schneider et al, 2005).…”
Section: Service Climate and Customer Citizenship Behaviormentioning
confidence: 99%
“…In addition, CCBs will be enhanced when there is a match between customer identity and organizational identity, or when the interdependent relationships exist between service organization and customers (Ahearne et al, 2005). If the customers receive more attention and responses from service firms, such as responding to customers' kind advice with timely measures, customers will be more active in services and voluntarily provide the enterprise with rationalization proposal (Mugambwa et al, 2016). In this way, the customer-enterprise relationship turns into a virtuous circle and service firms will finally benefit from their effort in service climate (Schneider et al, 2005).…”
Section: Service Climate and Customer Citizenship Behaviormentioning
confidence: 99%
“…[4] concluded that staff was the most important dimension in explaining the willingness to recommend hostels. In the past decades, numerous studies have focused on issues relating to residents' satisfaction; however, there are still gaps in the literature since the field of campus safety still growing in countries [11]. The present study fills the gap in the literature by addressing the determinants of residents' satisfaction in the metropolitan city of a developing country i.e., Pakistan.…”
Section: Literature Reviewmentioning
confidence: 94%
“…When discussing a product or service, being affirmed by others will enhance the user's feeling of being "empowered" and encourage the user to recommend the product or service to other users inside and outside the community. At the same time, if users receive more attention and a positive response, they will more actively participate in the interaction and voluntarily provide help and rationalization suggestions [34]. In this way, a virtuous circle is formed, enabling the virtual community to benefit from this environment.…”
Section: Customer Citizenship Behaviormentioning
confidence: 99%